Corpus Inscriptionum Arabicarum Palaestinae : j (1). - Sharon, Moshe. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2017)
Western Palestine is extremely rich in Arabic inscriptions, whose dates range from as early as CE 150 until modern times. Most of the inscriptions date from the Islamic period, for under Islam the country gained particular religious and strategic importance, even though it made up only part of the larger province of Syria. This historical importance is clearly reflected in the hundreds of inscriptions, the texts of which cover a variety of topics: construction, dedication, religious endowments, epitaphs, Qur'anic texts, prayers and invocations, all now assembled in the Corpus Inscriptionum Arabicarum Palaestinae ( CIAP ). The CIAP follows the method established at the end of the 19th century by Max van Berchem, namely, the studying of the Arabic inscriptions 'in context'. Van Berchem managed to publish two volumes of the inscriptions from Jerusalem: the CIAP covers the entire country. The inscriptions are arranged according to site, and are studied in their respective topographical, historical and cultural context. In this way the CIAP offers more than a survey of inscriptions: it represents the epigraphical angle of the geographical history of the Holy Land. Volume One: A, was published in 1997, Volume Two: -B-C- in 1999, Volume Three: -D-F- in 2004, Volume Four: G in 2008, an Addendum in 2007 and Volume Five: -H-I- in 2013. All volumes are still available.